Examining Alphabet Writing Fluency in Kindergarten: Exploring the Issue of Time on Task. (March 2017) - Puranik, Cynthia S.; Patchan, Melissa M.; Sears, Mary M.; McMaster, Kristen L.
Curriculum-based measures (CBMs) are necessary for educators to quickly assess student skill levels and monitor progress. This study examined the use of the alphabet writing fluency task, a CBM of writing, to assess handwriting fluency—that is, how well children access, retrieve, and write letter forms automatically. In the current study, the alphabet writing fluency task was administered at both the beginning and end of the kindergarten school year. Scores were calculated for two time increments, 15 and 60 s, and compared with an alphabet writing, untimed task. All three scores were compared with criterion measures of writing, including both standardized writing assessments and compositional CBMs of writing. Results indicate that measuring alphabet writing fluency using either timed tasks (15- or 60-s) at the beginning or the end of kindergarten may not be a useful or valid endeavor. In contrast, the alphabet writing, untimed task measure showed stronger correlations to criterion writing measures in comparison with the 15- and 60-s alphabet writing fluency tasks and also showed greater concurrent and predictive validity. Limitations and further areas of study are discussed.